Punishment In Islamic Education Perspective - lailul ilham (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2021)
In the world of education giving punishment is natural because, in addition to educating, punishment is also part of the education services provided in different ways (sanctions). In general, the basic principle of punishment is education. Then in the study of Islamic education, punishment is a legitimate act, even in Islam the type of punishment in the form of exile, beating, etc. is explained, this fact shows that Islam requires the practice of giving punishment in the context of education. Then the advantage is punishment in the perspective of Islam is not only explained as sanctions in anticipating or overcoming the problem of student violations. But far from that, Islam also emphasizes the rules in imposing penalties, the rules are in the form of stages and mechanisms in providing punishment as well as the limitations that must be considered in providing punishment, both in aspects of the type of punishment, quality of punishment, and intensity of punishment. Studies and discussion related to punishment in an Islamic perspective are important to continue to be carried out as an effort to maintain the spirit of Islamic education and education in general, maintain the charism of educators, as well as to anticipate the occurrence of punishment beyond the limits or violence in education. Keywords: Punishment, Education, and Islam